Hubungan Kompetensi Kepribadian Mahasiswa Guru dengan Motivasi Berprestasi Siswa [Relationship between Student Teacher’s Personality Competence and Student’s Motivation of Achievement] - Budi Wibawanta; Novemelia Purba (Polyglot, 2017)
The role of teachers is not merely transferring knowledge, but also developing student character. In the field, students tend to do only the minimum necessary to pass. The objectives of this study were to determine if there was a correlation between student-teacher personality competence and student motivation, specifically their achievement motivation. The level of the significance of the correlation was also investigated. This research was a quantitative research correlational design with a 0.05 level of significance. Spearman Rank correlation coefficient test and SPSS program were used to analyze the data. The population of this research was 88 students, while the samples taken were 22 students by using purposive sampling technique. The results of this research confirmed that there was a positive correlation between student-teacher personality competence and students achievement motivation. Furthermore, the correlation between student-teacher personality competence and students achievement motivation was significant.BAHASA INDONESIA ABSTRAK: Peran guru bukan hanya sekadar mentransfer ilmu, melainkan juga mendidik karakter siswa. Di lapangan, siswa menunjukkan bahwa mereka hanya mengejar Kriteria Ketuntasan Minimum (KKM) di dalam kelas untuk lulus. Tujuan penelitian ini adalah untuk mengetahui adanya hubungan antara kompetensi kepribadian mahasiswa guru yang sedang praktik mengajar dengan motivasi berprestasi siswa serta mengetahui signifikansi hubungannya. Penelitian ini merupakan penelitian kuantitatif desain korelasional dengan taraf signifikansi 0.05. Uji koefisien korelasi Spearman Rank dan program SPSS digunakan untuk menganalisis data. Jumlah populasi penelitian ini adalah 88 siswa, sementara sampel yang diambil sebanyak 22 siswa dengan menggunakan teknik purposive sampling. Hasil penelitian ini menunjukkan bahwa terdapat hubungan positif antara kompetensi kepribadian mahasiswa guru dengan motivasi berprestasi siswa. Hubungan kompetensi kepribadian mahasiswa guru dengan motivasi berprestasi siswa ini dinyatakan signifikan.